Análise do efeito da auriculoacupuntura em pacientes com doença renal e dor musculoesquelética crônicas: ensaio clínico randomizado - Melo, Geórgia Alcântara Alencar (2020)
Introduction: chronic pain is common in patients with chronic kidney disease. Therefore, complementary therapies are part of the non-pharmacological measures in pain control, besides presenting lower risk, low cost and being less invasive. Among them, auriculoacupuncture stands out. Objective: to analyze the effect of auriculoacupuncture on chronic musculoskeletal pain in renal patients on hemodialysis. Method: randomized, controlled, blind ed trial conducted in two hemodialysis clinics. The study included two groups, totaling 94 patients, randomized into blocks, allocated in a ratio of 1:1, in which the intervention group received ear acupuncture (AA) and the control group, placebo acupuncture (SAA). The intervention group received 12 sessions of auriculoacupuncture during dialysis therapy for 12 consecutive weeks. The intervention consisted of the application of adhesive spheres in the shenmen, tranquilizer, thalamus, sympathetic, scratch point, kidney, spleen, liver and lumbar vertebrae. The control group received the same follow-up, but with the spheres, at the following points: tonsil, esophagus, genitals, scaly and helix 4. The size and model of the spheres were identical. The data analysis instruments were: Visual Analog Pain Scale (VAS) and Mc Gill's questionnaire for pain; Rolland Morris Scale for disability and Pittsburg Sleep Quality Index (PSQI) for sleep. In the analysis, the following tests were used: t Pareado, Wilcoxon, ANOVA and Cohen's D. Results: the variation between the median pain score in the initial and final moments was Δ=+0.4 (p=0.931) in the SAA and Δ=-5.89 (p<0.001) in the AA (VAS); Δ=-8.78 (p<0.001) in SAA and Δ=- 28.40 (p<0.001) in AA (McGill). Regarding disability, the variation was Δ=-3.02 (p=0.008) in SAA and Δ=-6.38 (p<0.001) in AA; and sleep Δ=-0.23 (p=0.102) in SAA and Δ=-6.80 (p<0.001) in AA. After the 12 sessions, the auriculoacupuncture reduced pain when compared to the SAA group measured by both the EVA Scale (63% F=38.09, p<0.001); mcgill (49% F=21.65, p<0.001). It also reduced disability (33% F=11.02, p<0.001) and improved sleep quality (109.1% F=109.1, p<0.001). A high magnitude of effect was found at the end of the 12 pain sessions measured by the EVA Scale (D=-1.93) and McGill (D=-1.34), as well as in the PSQI (D=-1.94). Regarding disability, a small magnitude of effect was observed (D=- 0.19). Conclusion: the auriculoacupuncture intervention showed a positive effect on reducing pain and disability and improving sleep quality of patients with renal disease and chronic musculoskeletal pain. REBEC: RBR:3cpwwt